Improving Arabic Academic Writing Skills Through Contextual Teaching And Learning Approach - Muhammad Kamal Abdul Hakim (Jurnal Alsinatuna, 2018)
The aim of this study is to examine the effect of contextual teaching and learning approach to the Arabic academic writing skills students of Education Arabic Department Faculty of Language and Arts State University of Jakarta. The research was conducted at the second semester in 2015/2016 academic year starting from February up June in 2016. The study design used Elliot’s procedure, which comprised seven phases, namely: (a) identifying the initial ideas, (b) finding and analyzing the facts, (c) general planning, (d) Implementing, (e) observing, (f) evaluating, and (g) revising. The data were taken by observation, interview, and test. The results of the study found that the mean of the pre-test was 65,30, the average score results of the test at the first cycle were 73,25, the average score of the test at the second cycle was 77,40, and the average score of the test at third cycle was 84.1. It concluded that contextual teaching and learning approach could improve the student’s skill in Arabic academic writing.